On the Challenges of Transcending Differences Established by Instances of Domination and Power - a Perspective on the Concept of Making Indifference Present - Orlik, Piotr (Sensus Historiae, 2022)
The analyses presented in the article are made from the perspective of the concept of making indifference present. The author reconstructs the stages of the creation of the above concept as well as the particular role played in this regard by a specific critical attitude, which is not destructive in nature, but constitutes - according to Husserl - “mutual help through criticism.” The possibilities of transcending the differences established by instances of domination and power are examined, with attention focused primarily on the determinants of political discourse and advertising. The analyses presented show that in the acts of anticipating indifference that embrace the differences outside the “self,” the subject of these acts becomes independent of external influences and gains power over itself, whereas the radicalization of these acts - at the moment of their embracing the fundamental and hitherto reinforced difference between “self” and “not-self” - puts their subject in question, thus posing a challenge to “consider one’s own Self as nothing.”